Ecocriticism of the Poem "Wajadtuhā" (I Found It) by Fadwa Tuqan and Its Relevance to the Socio-Ecological Crisis of the Sea Wall Project in Indonesia - Majda Qudsiyatul Malikh; Alvira Nirma Wijayanti; Dafa Aqila Musyaffa (El-Syaker : Samarinda International Journal of Language Studies, 2025)
This study analyzes the poem “Wajadtuhā” (I Found It) by Fadwa Tuqan by combining the ecocritical approach of Glotfelty and Fromm with Braun and Clarke’s thematic analysis method. This topic was chosen because the poem presents ecological symbolism that is relevant to socio-ecological crises, particularly in the context of the Sea Wall Project in Indonesia. The main objective of this research is to reveal how the poem fosters ecological awareness and illustrates the relationship between human inner experience and nature. This study employs a descriptive qualitative method. Data were collected through documentation of the poem's text, ecocritical theories, and contextual data from news and environmental policies. To ensure data validity, theory and source triangulation were applied, along with increased rigor through repeated readings and peer discussions. The data analysis followed five stages: comprehensive reading of the text, identifying ecological elements, grouping themes, analyzing ecopoetic aspects, and relating the findings to the context of the Sea Wall Project. The results identified five main themes: ecological healing, resilience, human exploitation, nature’s restoration, and ecological spirituality. Its relevance to the Sea Wall Project is reflected in the critique of the imbalanced human-nature relationship, resistance to the marginalization of coastal ecosystems, and the poem’s voice as a symbolic form of advocacy for ecological rights threatened by development. The poem portrays nature as an existential partner that provides space for reflection and healing, rather than a passive object. These findings affirm that Tuqan’s work is an ecopoetic reflection that raises ecological awareness and critiques environmental exploitation in coastal development.